A Critical Analysis of Qaysari’s School of Thought and Clarification of Imam Khomeini’s Views on Criterion for Classifying Divine Names as Immanent, Attributes and Actions - Seyed Reza Eshaqnia (پژوهش‌نامه متین, 2021)
In theoretical mysticism, the Glorious Names of God fall into immanent names, attributes and actions. In his commentary to Fusus al-Hikam (The Seals of Wisdom), Qaysari argues that this categorization of names helps manifestation of God’s inherent nature, attributes, and actions in each name. According to this viewpoint, if the attribution of a name means inherent nature, that name shall be considered immanent and if it denotes quality and action it must be considered among attributes or actions of God. In his notes on commentaries about Fusus al-Hikam, Imam Khomeini says such classification is in no way according to the principles of mysticism. He then offers another criterion that goes well with the tenets of mysticism. In his view, the manner of classification, observations of the wayfarer in stages of spiritual journey and the quality of annihilation in God take place in actions, attributes and inherent nature of God. On this basis, whatever the wayfarer observes at the stage of annihilation in action, shall be considered an instance of action and whatever taking place as annihilation in attributes and inherent nature of God shall be considered among attributes and immanent names. In this research work, we have first developed a critical approach toward Qaysari’s viewpoints and then continued with clarification of Imam Khomeini’s theory. To that end, further explanation of the four entries namely types of monotheism in mysticism, inherent annihilation, four mystical journeys, and ranks of intuitive faith is necessary.